In vitro evaluation of dihydropyridine-3-carbonitriles as potential cytotoxic agents through PIM-1 protein kinase inhibition - Abnous, Khalil (Res Pharm Sci, 2017)
PIM-1 protein kinase inhibitor belongs to a novel class of serine/threonine kinases. As PIM-1 is overexpressed in cancer cells and possesses oncogenic functions, its inhibition provides a new option in cancer therapy. In this study, in vitro inhibitory effects of seven analogues of 1, 2-dihydropyridine-3-carbonitrile derivatives Ia-c, IIa-d on the activity of recombinant PIM-1 were evaluated using dimethylthiazol diphenyltetrazolium bromide (MTT) assay. The PIM-1 protein kinase inhibitory potencies and the cytotoxicity effects of tested compounds were respectively as follows: Ic > IIa > Ia > IIb > Ib > IId > IIc and IIb > IIa > Ia > IIc > Ic > Ib > IId, respectively. The compound Ic with methylthio imidazole substituent at C-3 position and benzodioxole substituent at C-6 position of 2-imino-1, 2-dihydropyridine-3- carbonitrile structure showed the strongest PIM-1 inhibitory effect (IC(50) = 111.01 nM), while the compound IIc with methythio imidazole substituent at C-3 position and benzodioxole substituent at C-6 position of 2-oxo-1, 2-dihydropyridine-3- carbonitrile structure exhibited the least inhibition activity (IC(50) = 433.71 nM). The docking results showed that all tested compounds localized appropriately in the middle of binding cavity after docking procedure, demonstrating suitable interactions between ligands and protein. This study demonstrated that the PIM-1 inhibitory potencies of newly synthesized compounds were in submicromolar concentrations (IC(50) < 150 nM) while they exhibited low cytotoxicity on HT-29 cell line (IC(50)> 130 μM). Altogether, our data indicated that compounds Ic, IIa, Ia could be considered as new potent non-toxic PIM-1 inhibitors which could be used in combination with routine anti-proliferative drugs.